Studies on Environmental and Applied Geomorphology - Piacentini, Tommaso; Miccadei, Enrico (IntechOpen, 2012)
This book includes several geomorphological studies up-to-date, incorporating different disciplines and methodologies, always focused on methods, tools and general issues of environmental and applied geomorphology. In designing the book the integration of multiple methodological fields (geomorphological mapping, remote sensing, meteorological and climate analysis, vegetation and biogeomorphological investigations, geographic information systems GIS, land management methods), study areas, countries and continents (Europe, America, Asia, Africa) are considered.